Pour une esthétique de l'émancipation: construire les lignées d'un art queer - Alfonsi, Isabelle; Fraisse, Geneviève; Abonnenc, Mathieu K. (Mathieu Kleyebe) (Culture, 2019)
"Loin de relire l'histoire de l'art en lui appliquant de façon anachronique le terme « queer », utilisé positivement dans les milieux militants depuis la fin des années 1980, Pour une esthétique de l'émancipation cherche à montrer comment l'écriture de l'Histoire de l'art a minoré l'importance des engagements politiques et affectifs des artistes et rendu inopérante la portée sociale de leurs œuvres. En imaginant des amitiés inédites entre des artistes du passé, Isabelle Alfonsi fait émerger une lignée féministe et queer pour l'art contemporain. Des pratiques artistiques du XXe siècle sont ainsi replacées dans le contexte du militantisme de défense des droits des homosexuel•le•s et de la formation d'une critique radicale féministe et anticapitaliste. Claude Cahun et Michel Journiac croisent l'histoire du minimalisme états-unien, vu à travers Lynda Benglis, Lucy Lippard ou Yvonne Rainer. Les guerres de représentation menées pendant la crise du sida sont lues au prisme des oeuvres de Felix Gonzalez-Torres, du concept de désidentification de José E. Muñoz et de l'activisme culturel du groupe Boy/Girl with Arms Akimbo, dans le San Francisco des années 1980."-- Résumé de l'éditeur.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; activisme; approches et analyses; artistes queers; arts; cours; discipline; har4600; histoire de l'art; histoire et politique; militance; premier cycle; périodes historiques; queer; thématiques; émancipation

Queer - Getsy, David (Whitechapel : documents of contemporary art, 2016)
"Rather than a book of queer theory for artists, this is a book of artists' queer tactics and infectious concepts. In the first such anthology to be centred on artists' writings, numerous conversations about queer practice are brought together from diverse individual, social and cultural contexts. Together these texts describe and examine the ways in which artists have used the concept of queer as a site of political and institutional critique, as a framework to develop new families and histories, as a spur to action, and as a basis from which to declare inassimilable difference"--Back cover.
Keywords: LGBTQIA2+; approches et analyses; arts; arts visuels et médiatiques; cours; critique institutionelle; critique politique; discipline; har4600; identités LGBTQIA2+; intersectionnalité; militance; pratique artistique; premier cycle; queer; thématiques; écrits d'artiste

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (Cultural front, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires